Effect of Vitamin E on Biochemical Parameters in Albino Rats Treated with Gasoline - George, M. I.; Adegoke, O. A. (Journal of Scientific Research, 2011)
The study was carried out to assess the effect of antioxidant vitamin E on the toxicity caused by gasoline in albino rats. The study was carried out by monitoring the aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (Alkphos), urea and creatinine in albino rats fed diet containing vitamin E to saturation and injecting gasoline intraperitoneally. It was observed that the LD100 and LD50 increased significantly in vitamin E fed rats compared to the gasoline fed rats. Also the enzymes monitored were reduced in vitamin fed rats compared with the gasoline fed rats while the kidney function improved with the vitamin E rats by the lowering of the urea and creatinine elevated by gasoline. This suggests that the vitamin E conferred some protection on the rats by its antioxidant nature. Therefore this study showed that gasoline as a free radical caused hepatotoxicity and renal damage while vitamin E can confer protection against toxicity caused by gasoline by donating an electron to stabilize the free radical and terminating the chain reaction before vital molecules are damaged. Hence feeding on diet containing vitamin E should be encouraged. Keywords: Hepatotoxicity; Gasoline; Antioxidant; Enzymes. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7671 J. Sci. Res. 3 (3), 651-659 (2011)